THE LIFE AND WORK OF ABDULLA AVLONI - J. SH. Mustafayev; U.F. Jozilov (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, the countries where Abdullah Avloni sought knowledge during his life and work, the spiritual heritage of his works, and the information that has reached us are described in this article.